A Randomized Trial of Cholecalciferol versus Doxercalciferol for Lowering Parathyroid Hormone in Chronic Kidney Disease - Moe, Sharon M. (American Society of Nephrology, 2010)
Background and objectives: The optimal treatment of secondary hyperparathyroidism in chronic kidney disease (CKD) is unknown. Design, setting, participants, & measurements: We conducted a randomized, blinded, 3-month trial in vitamin D-deficient CKD stage 3 and 4 patients with parathyroid hormone (PTH) values above the Kidney Disease Outcomes Quality Initiative target, comparing cholecalciferol (4000 IU/d × 1 month, then 2000 IU/d; n = 22) to doxercalciferol (1 μg/d; n = 25). Results: There was no difference in baseline demographics or lab tests, except a slightly higher estimated GFR (eGFR) in the doxercalciferol group. There was a significant increase in vitamin D level in the cholecalciferol group (14 ± 6 to 37 ± 10 ng/ml; P < 0.001) but no change in the doxercalciferol group. The PTH decreased by 27% ± 34% in the doxercalciferol group (P = 0.002) and decreased by 10% ± 31% in the cholecalciferol group (P = 0.16), but the difference between treatments was NS (P = 0.11). Similar results were found when absolute PTH change from baseline to end point was analyzed in a repeated-measures ANOVA model. The serum calcium and urine calcium excretions were not different. Additional non-mineral-related end points, albuminuria, and BP were evaluated, and although trends were present, this did not reach significance. Conclusions: This prospective, randomized trial demonstrated a within-group reduction in PTH in the doxercalciferol-treated patients but no significant difference between the doxercalciferol and cholecalciferol patients. Larger, long-term studies are needed to demonstrate efficacy of mineral-related and non-mineral-related end points and safety.